How Blocking Distractions Affects Workplace Focus and Productivity - Mark, Gloria; Iqbal, Shamsi; Czerwinski, Mary (UBICOMP/ISWC '17 Adjunct Proceedings, 2017)
Information workers are faced with ever-increasing online distractions in the workplace. Website blockers are one solution toward preventing unwanted distractions. We conducted an in situ field study with 32 information workers in their workplace to test if the use of blocking software can increase focus and productivity by preventing non-work-related distractions. Participants worked for five days in a baseline condition and then worked five days where online distractions were blocked with software. We discovered that with blocking software, participants assessed their productivity significantly higher and could focus significantly longer. People who benefited the most from the software were those who were most distracted by social media. Interviews revealed individual differences in self-control in managing distractions. Resultant changes in work behaviors included switching from online distractions to physical breaks of leaving the office. An unexpected consequence of cutting off distractions for people with less self-control was that they were more focused and worked longer without taking breaks and therefore, experienced higher stress. We present design recommendations to promote focus for the variety of coping behaviors we observed.